2018
DOI: 10.1177/1753193418765716
|View full text |Cite
|
Sign up to set email alerts
|

Lumbrical muscle tear: clinical presentation, imaging findings and outcome

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Due to its bipennate connection to FDP tendons III and IV, the third lumbrical muscle is at risk of rupture if affected by increased transverse tension, for example in free climbers [61,62]. The muscle rupture can be visualized on high-resolution T2-weighted images by means of muscle edema and fiber discontinuity.…”
Section: Injury Of the Third Lumbrical Musclementioning
confidence: 99%
“…Due to its bipennate connection to FDP tendons III and IV, the third lumbrical muscle is at risk of rupture if affected by increased transverse tension, for example in free climbers [61,62]. The muscle rupture can be visualized on high-resolution T2-weighted images by means of muscle edema and fiber discontinuity.…”
Section: Injury Of the Third Lumbrical Musclementioning
confidence: 99%
“…This explains why strain injuries occur most often to the third and fourth lumbricals, which are commonly bipennate. Rest and immobilization have been suggested to be sufficient to treat lumbrical sprain ( 17 ) . Atrophic changes may be found affecting the first and second lumbricals in median neuropathies and in the third and fourth lumbricals in ulnar neuropathies ( 18 , 19 ) .…”
Section: Lumbricalsmentioning
confidence: 99%
“…Lutter et al (18) suggested 4 wk of functional therapy for a grade 1 injury. A grade 2 injury should be treated with 8 wk of therapy and the addition of “buddy taping” of the affected digit for pain reduction.…”
Section: Finger and Wristmentioning
confidence: 99%
“…A grading system was proposed in a study by Lutter et al (18). A grade 1 injury consists of microtrauma without imaging findings.…”
Section: Finger and Wristmentioning
confidence: 99%